Survey of Economic and Social Developments in the Arab Region 2016-2017 - United Nations Economic; Social Commission for Western Asia (United Nations, 2018)
This publication focuses on the analysis of the most recent socioeconomic developments in two ways. The first focus aims at demonstrating the analytical observation of routinely monitored economic and social variables of the Arab region in the global context (the monitoring part). The second focus aims at an in-depth analysis on the regional impacts of ongoing fiscal reforms (the thematic part).